The Landing Error Scoring System Real-Time test as a predictive tool for knee injuries: A historical cohort study. (March 2020) - Schwartz, Oren; Talmy, Tomer; Olsen, Cara H.; Dudkiewicz, Israel
Abstract: Purpose: To assess the value of the Landing error score system - real time test as a predictive tool for knee injuries among combat soldiers in the Israeli defense forces. Methods: All 2474 Israeli defense forces' combat soldiers enrolled at the Israeli defense forces Injury Prevention and Rehabilitation Center were included. A retrospective cohort study was conducted. The predictive variable assessed was the landing error score system – real time score. The three main outcome variables were the incidence of overuse knee injuries, the meniscal injury, and the anterior cruciate ligament injury. Receiver operator characteristic analysis was performed to evaluate the test's potential as a predictive tool and in order to establish optimal cutoff scores. Results: The area under the curve of the receiver operation curves demonstrated no predictive value of the landing error score system – real time test for all three outcome variables (knee injuries: area under the curve 0.526, 95% confidence interval 0.498, 0.554, anterior cruciate ligament injuries: area under the curve 0.496, 95% confidence interval 0.337, 0.656, meniscus injuries: area under the curve 0.515, 95% confidence interval 0.454, 0.576). Interpretation: Based on the results of this study, the landing error score system – real time test has no predictive value for knee overuse injuries, meniscal injuries, and anterior cruciate ligament injuries. However, due to the small number of cases of anterior cruciate ligament injuries, the predictive value for anterior cruciate ligament injuries of this test should be further investigated. Highlights: The investigated test demonstrated no predictive value for overuse and meniscus knee injuries. The predictive value of this test should be further investigated. The need for a screening test for anterior cruciate ligament injury is questionable.